2008
DOI: 10.1128/jcm.00799-08
|View full text |Cite
|
Sign up to set email alerts
|

Acne is Not Associated with Yet-Uncultured Bacteria

Abstract: Current clinical and microbiological information on acne fails to demonstrate a clear association between particular species, including Propionibacterium acnes, and disease, and the disease continues to be a considerable problem. To test if acne is associated with hitherto uncultured bacteria residing in diseased skin follicles, sequencing and phylogenetic analysis of approximately 5,700 amplified and cloned 16S rRNA genes were used to determine the microbial diversity in follicles from acne patients and healt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
96
2
4

Year Published

2014
2014
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 131 publications
(109 citation statements)
references
References 38 publications
7
96
2
4
Order By: Relevance
“…In general, all case–control studies demonstrated similarly an increased microbial abundance of Propionibacterium acnes in the skin microbiome of patients with AV, compared to healthy 51, 52, 53. In addition, an association between a specific P. acnes strains and acne affected skin, and healthy skin respectively was demonstrated 51, 52. Acne improved and Propionibacterium abundance decreased after various treatments, together with an increase of microbial diversity in the two controlled studies.…”
Section: Resultsmentioning
confidence: 56%
See 2 more Smart Citations
“…In general, all case–control studies demonstrated similarly an increased microbial abundance of Propionibacterium acnes in the skin microbiome of patients with AV, compared to healthy 51, 52, 53. In addition, an association between a specific P. acnes strains and acne affected skin, and healthy skin respectively was demonstrated 51, 52. Acne improved and Propionibacterium abundance decreased after various treatments, together with an increase of microbial diversity in the two controlled studies.…”
Section: Resultsmentioning
confidence: 56%
“…Three (3) were case–control studies and two (2) were small single‐centre, controlled studies, of whom one was a double‐blind, randomized‐controlled trial. In general, all case–control studies demonstrated similarly an increased microbial abundance of Propionibacterium acnes in the skin microbiome of patients with AV, compared to healthy 51, 52, 53. In addition, an association between a specific P. acnes strains and acne affected skin, and healthy skin respectively was demonstrated 51, 52.…”
Section: Resultsmentioning
confidence: 59%
See 1 more Smart Citation
“…Antibacterial activity test from ethyl acetate fraction of green tea leaves extract with buffer solution pH 4 methods in Propionibacterium acnes ATCC 6919: Propionibacterium acnes ATCC 6919 is a Gram-positive bacterium which is a facultative anaerobic bacteria that cause acne specific (Bek-Thomsen et al, 2008).…”
Section: Phosphate Acid (%) -----------------------------------------mentioning
confidence: 99%
“…These results clearly exclude the possibility that yet-uncultured bacteria are associated with acne-affected skin follicles. [2] Propionibacterium acnes play a central role in acne pathogenesis. Not only does this anaerobic bacterium produce lipases, proteases, and other extracellular enzymes, it also secretes chemotactic factors attracting polymorphonuclear leukocytes, lymphocytes, and macrophages.…”
Section: Discussionmentioning
confidence: 99%